1999
DOI: 10.1080/03009749950155472
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of renal biopsy and clinical variables in patients with lupus nephritis and normal serum creatinine

Abstract: Early renal biopsy and the abovementioned signs of active renal disease carry prognostic information that may have significant therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Few studies in the pediatric literature have analyzed the risk factors for renal failure in childhood LN. Our results confirm and support the previous observations that several clinical indicators of disease severity are potentially important prognostic factors [1, 4, 15, 16, 21, 27]. We demonstrated that those with class IV LN, impaired renal functions or nephrotic syndrome at initial evaluation were at high risk for reaching the endpoints of renal failure or death despite all aggressive treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Few studies in the pediatric literature have analyzed the risk factors for renal failure in childhood LN. Our results confirm and support the previous observations that several clinical indicators of disease severity are potentially important prognostic factors [1, 4, 15, 16, 21, 27]. We demonstrated that those with class IV LN, impaired renal functions or nephrotic syndrome at initial evaluation were at high risk for reaching the endpoints of renal failure or death despite all aggressive treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Histopathological findings and demographic data including race, age, sex, clinical and serological features have been investigated to predict the prognosis of LN in adults and also children [5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 21, 22]. The results still remain controversial, and most authors consider the presence of class IV (diffuse proliferative) nephritis, high creatinine clearance ratio (Ccr), persistent hypertension, the age of onset before 12 years, male sex and black race as significant poor prognostic parameters of LN [4, 9, 10, 12, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in outcomes of immunosuppressive treatment of patients with lupus nephritis, renal remission is obtained in less than 50% of cases within 2 years; approximately 10% may progress to end-stage renal disease [83,84], which is associated with significantly increased rates of cardiovascular mortality [85]. In general, patients with SLE and renal involvement have more cardiovascular disease than the remaining SLE patients [86,87].…”
Section: Potential Implications Of Data On Murine Lupus Nephritis Formentioning
confidence: 99%